Botulinotherapy and Orthopedic Interventions After Selective Dorsal Rhizotomy in Children with Cerebral Palsy: Cohort Study - Olga A. Klochkova; Ekaterina I. Smolyankina; Dmitriy Yu. Zinenko; Ayaz M. Mamedyarov; Ulviya Sh. Ashrafova (Вопросы современной педиатрии, 2025)
Background. Selective dorsal rhizotomy (SDR) is an effective neurosurgical method for reducing spasticity in children with cerebral palsy (CP). The need for other medical (anti-spastic) and surgical treatment methods after SDR remains poorly studied. Objective. Aim of the study is to evaluate the frequency of using botulinum therapy and orthopedic interventions, as well as target muscles selection for injection in patients with cerebral palsy after SDR. Methods. Prospective cohort study included patients under the age of 18 years after SDR performed between January 2021 and June 2023. Frequency, timing, target muscles for botulinotherapy, oral anti-spastic drugs administration, as well as frequency, timing, and type of orthopedic surgeries (year after rehabilitation due to performed SDR) were determined via interviewing (remote or face-to-face) of patients’ legal representatives. Results. The study included data from 107 children with spastic cerebral palsy (GMFCS I — 2, GMFCS II — 14, GMFCS III — 68, GMFCS IV — 22, GMFCS V — 1) who underwent SDR at median age of 5.0 (3.9; 6.9) years. The follow-up period after SDR was 12–41 months, median was 20.8 (16.5; 26.7) months. Botulinotherapy was performed in 24 (22.4%) patients (4 for the first time) after SDR, the initiation period was 1.5–36 months after SDR, the median was 10.7 (6.9; 16.4) months. Injections were performed only in the arm’s muscles in 4 children, only in leg’s muscles — in 10, in upper and lower limbs — in 10, in salivary glands — in 1 case. Orthopedic surgeries were performed in 26 (24.3%) cases 3.5–34 months after SDR, median — 14.8 (8.0; 22.6) months. Procedures on soft-tissues of lower limbs were performed in 17 patients, 9 patients had combined soft tissue and bone surgery. Age at surgery was 3.3–12.7 years, median age — 5.9 (5.0; 8.5) years. Oral myorelaxant administration after SDR (continued) was reported only in one patient. Conclusion. Some patients with cerebral palsy require implementation of other methods for spasticity and orthopedic deformities correction even after SDR due to the child growth.